Manifestasi Ibnu Hibban Terhadap Metodologi Penulisan Kitab Shahih Ibnu Hibban - Jasmit, Rudi Edwaldo; Kusuma, Febri (EL-EMIR Institute, 2024)
This article reviews the systematics, writing/compilation methods and introduces the book of Sahih Ibn Hibban in a more comprehensive manner which is different from the habits of the muhaddits in compiling their works in the collection of Hadith of the Prophet sallallaahu 'alaihi wa sallam. This cannot be separated from his background and his motives (goals) in collecting and compiling Hadith. In addition, Sahih Ibn Hibban in terms of its name is not as it is currently known by the public, because the original title of the book was